Critical Thinking Skills through Problem Based Learning Model - Fitriyani, Yani; Supriatna, Nana; Sari, Mia Zultrianti (International Conference on Elementary Education, 2021)
Education in the era of the industrial revolution 4.0 requires students to have higher-order thinking skills. One of the high-level skills that students must have is critical thinking skills. These skills are one of the important skills in increasing the ranking of Indonesia's PISA (Program for International Student Assessment) which is still relatively low, so a learning model is needed that can affect students' critical thinking abilities. This study uses literature studies to describe the effectiveness of problem-based learning models on critical thinking skills in social science learning in elementary schools. After the researchers conducted a literature review from various sources. The research results found that the problem-based learning model has an effective influence on students' critical thinking skills in social science learning. The conclusion of the research results shows that educators play an important role in implementing and designing innovative learning models so that they can foster students' critical thinking skills in social science learning in elementary schools.